The Role of Pragmatic Strategies on University Campaign - Yunika Triana; Maftukhin Maftukhin; Arif Nugroho (NOTION: Journal of Linguistics, Literature, and Culture, 2022)
This paper aims to provide information that pragmatic strategies is needed to offer university campaign and branding. Researcher used Aristotle’s argumentation, ethos, logos and pathos to gain target audiences at Universitas Raden Mas Said Surakarta website. The advertisement in the form of word organization that was distributed with Google Ads. It is perceived that this practical application will improve attention and awareness of google users. Narrative design was conducted to find the answers associated to the research problem and the result was analyzed using rhetorical discourse analysis. It revealed that the word form, word organization, and context are able to influence the audience. All of these techniques use a pragmatic strategy approach where the advertiser does not invite the target audience directly, but the university and the target audience are brought together based on core of (word organization) supply and (audiences’ need) demand. This way is very efficient and effective to use during the covid-19 outbreak. This is also a reflection that conventional advertising has begun to be replaced by digital advertising. If compared to the previous year, there will be a 41% increase in registrants in 2021. This strategy has a significant impact and is very influential.